Strategy for Small Industry Development for Processing of Soybean-Based Tempeh From the Peatlands of Palangka Raya City: Strategi Pengembangan Industri Kecil Pengolahan Tempe Berbahan Baku Kedelai dari Lahan Gambut Kota Palangka Raya - Saputera; Herry Palangka Jaya; Yuliana (Journal of Peat Science and Innovation, 2022)
This study aims to determine the internal and external factors that can influence the development of the tempe processing industry and find out alternative strategies that can be applied in developing the tempe industry made from soybeans from the peatlands of Palangka Raya City. Data analysis was carried out using SWOT analysis to evaluate strengths, weaknesses, opportunities, and threats in the strategic planning of a small industry for processing tempeh made from soybeans from peatlands. The results of the analysis show that there are several internal and external factors that influence the development of the tempe processing industry made from soybeans from the peatlands of Palangka Raya City. There are several alternative strategies that can be implemented in developing the tempe industry made from soybeans from the peatlands of Palangka Raya City, namely maintaining the quality of tempe starting from taste, texture, aroma, improving business capital, human resources and raw materials in order to meet the high demand for tempe.